2013
DOI: 10.1021/ic302340c
|View full text |Cite
|
Sign up to set email alerts
|

cRGD Peptide-Conjugated Icosahedral closo-B122- Core Carrying Multiple Gd3+-DOTA Chelates for αvβ3 Integrin-Targeted Tumor Imaging (MRI)

Abstract: A vertex-differentiated icosahedral closo-B122− core was utilized to construct a αvβ3 integrin receptor-targeted (via cRGD peptide) high payload MRI contrast agent (CA-12) carrying 11 copies of Gd3+-DOTA chelates attached to the closo-B122− surface via suitable linkers. The resulting polyfunctional MRI contrast agent possessed a higher relaxivity value per-Gd compared to Omniscan, a small molecular contrast agent commonly used in clinical settings. The αvβ3 integrin receptor specificity of CA-12 was confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 43 publications
1
30
0
Order By: Relevance
“…211 While the per Gd(III) relaxivity of the scaffold containing macrocyclic Gd(III)-DO3A chelates ( q = 1) was notably lower (6.2 mM −1 s −1 ), this still represents a significant improvement over the monomeric complexes. 210 …”
Section: Lanthanide Probes For Mr Imagingmentioning
confidence: 99%
“…211 While the per Gd(III) relaxivity of the scaffold containing macrocyclic Gd(III)-DO3A chelates ( q = 1) was notably lower (6.2 mM −1 s −1 ), this still represents a significant improvement over the monomeric complexes. 210 …”
Section: Lanthanide Probes For Mr Imagingmentioning
confidence: 99%
“…After the successful development of the synthetic pathway and preparation of heterofunctional closomers, a number of articles were dedicated to the creation of complex systems bearing therapeutic or diagnostic, as well as tracking or directing, functions. The first example of such closomers contained eleven Gd 3+ ‐DOTA‐based CA molecules and a directing moiety – a cyclic derivative of the RGD peptide cyclo‐RGDfK . Previously, it was demonstrated that the attachment of contrast agent moieties to the closomer core significantly increases the MRI contrast , .…”
Section: Third Closomer Generation: Complex Delivery Vehicles Perfmentioning
confidence: 99%
“…For closomer 99 , the increase in relaxivity was not as dramatic (4.7 m m –1 s –1 ); however, both closomers 98 and 99 showed very low toxicity and extended circulation times , . The possibility of carrying a targeting unit has made closomer‐based contrast reagents very attractive diagnostic tools for certain types of tumors . Closomer 113 not only demonstrated an increased relaxivity compared to Omniscan (5.9 m m –1 s –1 vs. 4.2 m m –1 s –1 ) but also high affinity to implanted tumors and longer contrast enhancement times.…”
Section: Potential Applications Of Closomersmentioning
confidence: 99%
“…In tumor cells expressing both α v β 3 and CD 13 , the two motifs of RGD and NGR can simultaneously bind to the target tissue, which enhances the incorporation of the contrast agent; the higher concentration of the contrast agent in the tumor area will improve imaging visibility. In this study, the targeting behavior of the contrast agent that we designed was examined using MDA-MB-231 human breast cancer cells (which overexpress α v β 3 ) (19,20) and PC-3 human prostate cancer cells (which overexpress CD 13 ) (21). 4,7,10- 3 ].…”
Section: Introductionmentioning
confidence: 99%